2006
DOI: 10.1021/jf0627672
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitory Profile of Catechins and Theaflavins

Abstract: To clarify the postprandial glucose suppression effect of flavonoids, the inhibitory effects of catechins and theaflavins against alpha-glucosidase (AGH) were examined in this study. It was initially demonstrated that theaflavins and catechins preferentially inhibited maltase rather than sucrase in an immobilized AGH inhibitory assay system. For the maltase inhibitory effects of theaflavins, the effects were observed in descending order of potency of theaflavin (TF)-3-O-gallate (Gal) > TF-3,3'-di-O-Gal > TF-3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
197
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(212 citation statements)
references
References 27 publications
11
197
2
2
Order By: Relevance
“…Modern studies have found that catechin is responsible for antioxidant activity, antimicrobial activity, anti-ageing and antidiabetic properties (Lambert and Yang, 2003;Liu et al, 2014). The potent antioxidant property of catechin reduces free radical damage to cells and prevents the oxidation of LDL, cholesterol and blood glucose level (Cooper et al, 2005;Matsui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Modern studies have found that catechin is responsible for antioxidant activity, antimicrobial activity, anti-ageing and antidiabetic properties (Lambert and Yang, 2003;Liu et al, 2014). The potent antioxidant property of catechin reduces free radical damage to cells and prevents the oxidation of LDL, cholesterol and blood glucose level (Cooper et al, 2005;Matsui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is estimated that 1.9 billion adults are overweight and 600 million are obese by 2014 (Hosseinpanah et al 2016). Meanwhile, metabolic syndrome can cause serious damage to body systems, such as blood vessels and nerves (Matsui et al 2007;Cohen and Goedert 2004). One of the major causes of the metabolic syndrome is excessive consumption of carbohydrates and triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a chronic disease caused by inherited or acquired deficiency in insulin secretion and by decreased responsiveness of the organs to secreted insulin. 2 Such a deficiency results in increased concentrations of glucose in the blood, which in turn damage many of the body systems, in particular the blood vessels and nerves. 3 It is currently growing at a rapid rate throughout the world, and it is the 16th leading cause of global mortality.…”
Section: Introductionmentioning
confidence: 99%